2019
DOI: 10.1534/genetics.118.301803
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Population Studies Uncover the Genome Structure and Genetic Basis of Xenobiotic and Host Plant Adaptation in the HerbivoreTetranychus urticae

Abstract: Pesticide resistance arises rapidly in arthropod herbivores, as can host plant adaptation, and both are significant problems in agriculture. These traits have been challenging to study as both are often polygenic and many arthropods are genetically intractable. Here, we examined the genetic architecture of pesticide resistance and host plant adaptation in the two-spotted spider mite, Tetranychus urticae, a global agricultural pest. We show that the short generation time and high fecundity of T. urticae can be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
117
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 79 publications
(135 citation statements)
references
References 84 publications
3
117
0
Order By: Relevance
“…In a recent study, using an SR‐VP‐derived inbred line, spirodiclofen resistance was mapped in high resolution to a number of genomic loci (QTL mapping), confirming its polygenic nature. None of the QTLs was associated with the CCE04 locus (located on pseudochromosome 1 at 2.39 Mb), but contained other interesting candidate genes: ACCase – the target of keto‐enol acaricides (on pseudochromosome 1 at 6.56 Mb), a region containing P450s (on pseudochromosome 1 at 24.13 Mb) belonging to the same P450 subfamily as CYP392E10, known to metabolize spirodiclofen and cytochrome P450 reductase (CPR) (on pseudochromosome 2 at 5.69 Mb) . On the other hand, it is still possible that these genomic loci harbor regulators (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, using an SR‐VP‐derived inbred line, spirodiclofen resistance was mapped in high resolution to a number of genomic loci (QTL mapping), confirming its polygenic nature. None of the QTLs was associated with the CCE04 locus (located on pseudochromosome 1 at 2.39 Mb), but contained other interesting candidate genes: ACCase – the target of keto‐enol acaricides (on pseudochromosome 1 at 6.56 Mb), a region containing P450s (on pseudochromosome 1 at 24.13 Mb) belonging to the same P450 subfamily as CYP392E10, known to metabolize spirodiclofen and cytochrome P450 reductase (CPR) (on pseudochromosome 2 at 5.69 Mb) . On the other hand, it is still possible that these genomic loci harbor regulators (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focus on the role of additional resistance mechanisms, more specifically the involvement of carboxyl/choline esterases (CCEs), for the following reasons: (i) classical genetics revealed that spirodiclofen resistance in T. urticae was not controlled by a single gene and suggested that additional mechanisms next to P450 metabolism are highly likely, which was confirmed by a recent quantitative trait locus (QTL) study; (ii) synergism experiments have previously pointed out the involvement of both P450s and CCEs in spirodiclofen resistance in spider mites, which was confirmed by enzymatic assays; and (iii) microarray analysis revealed that a single CCE gene ( CCE04 ) was highly overexpressed in two genetically distinct T. urticae strains (SR‐VP and SR‐TK), while transcriptome analysis of a spirodiclofen‐resistant P. ulmi strain revealed that the overexpression of a CCE was strongly associated with spirodiclofen resistance …”
Section: Introductionmentioning
confidence: 98%
“…The two-spotted spider mite is a tractable organism for characterizing resistance mechanisms, as its haplodiploid breeding system (males are haploid while females are diploid) facilitates inbred line construction, its genome size is small (~90Mb), the generation time is as little as a week at optimal temperatures, and very large populations can be propagated (Van Leeuwen and Dermauw, 2016). Bulked segregant analysis (BSA) approaches have been used with T. urticae to identify monogenic loci (Bryon et al, 2017;Demaeght et al, 2014;Van Leeuwen et al, 2012), and these methods were recently extended to successfully describe polygenic resistance to a lipid-synthesis inhibiting acaricide, spirodiclofen (Wybouw et al, 2019). For genetic mapping of resistance with BSA methods, a resistant parent is crossed with a sensitive one, and resultant populations are expanded and selected with the pesticide.…”
Section: ) Introductionmentioning
confidence: 99%
“…From the resulting 1,150,705 nucleotide positions, 196,214 single nucleotide polymorphisms (SNPs) within T. kanzawai were identified as fixed for contrasting differences between the two parents, and were retained. The locus responsible for the lemon phenotype was identified by comparing allele frequencies between the three lemon selected samples to the wild-type sample using previously published BSA genetic mapping methods with statistical testing for genotype-phenotype associations by permutation [22]; 75 kb windows with 5 kb offsets were used with the false discovery rate (FDR) set to 5%. Genome annotation of the BSA peak was based on Wybouw et al [22].…”
Section: (D) Bsa Experimental Set-up Genomic Sequencing and Variant mentioning
confidence: 99%
“…The locus responsible for the lemon phenotype was identified by comparing allele frequencies between the three lemon selected samples to the wild-type sample using previously published BSA genetic mapping methods with statistical testing for genotype-phenotype associations by permutation [22]; 75 kb windows with 5 kb offsets were used with the false discovery rate (FDR) set to 5%. Genome annotation of the BSA peak was based on Wybouw et al [22]. (f) De novo assemblies DNA sequence reads were imported into CLC Genomics Workbench 9.0.1 (https://www.qiagenbioinformatics.com/), trimmed using default settings, assembled into contigs using the default settings of the "De Novo Assembly" tool, and the contigs were aligned to the T. urticae genome assembly using BLASR (version 1.3.1) [30].…”
Section: (D) Bsa Experimental Set-up Genomic Sequencing and Variant mentioning
confidence: 99%